KGB against Vilnius pupils in the 9th decade - Žiūkas, Mindaugas (Genocidas ir rezistencija, 2000)
The article analyses one of the spheres of the KGB activities in the Lithuanian SSR, i.c. “fight against nationalism and anti-Soviet activities”. Although young people made a considerable contribution to national and anti-Soviet movement in Lithuania, the subject has not yet been exhaustively investigated. Except few available scientific publications, the author, for the most part, referred to material culled from the Special Archive of Lithuania. Since the article focuses on the activities of the Vilnius City KGB Office, a short description of the Office's scheme, its functions and fields of work is being discussed after a short presentation of a general scheme of the KGB, as well as “hostile acts” of school students against the Soviet system and the KGB's retaliatory actions against the “offenders”.
Keywords: KGB; Vilnius; youth; pupils; KGB methods